2013
DOI: 10.1002/pam.21724
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Unconditional Quantile Regression to Cigarette Taxes

Abstract: This study investigates heterogeneous response to state cigarette tax increases using unconditional quantile regression (UQR). We make two contributions to the empirical policy analysis literature. First, we argue that UQR provides more policy‐relevant information than conventional quantile regression in most empirical state policy analyses. Second, we document cigarette tax elasticity across a sample of adult smokers in the Current Population Survey Tobacco Use Supplements between 1992 and 2011. Our ordinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 61 publications
(82 reference statements)
11
53
0
Order By: Relevance
“…Two exceptions are Laporte et al (2010), who use quantile regression and panel data from Canada to estimate a rational addiction model of smoking, and Maclean et al (2014). Maclean et al (2014) estimate smokers' responses to tobacco control policies using data from the Tobacco Use Supplement to the Current Population Survey (CPS-TUS). Using unconditional quantile regression, they find that smokers in the middle of the smoking distribution, smoking between 10 and 20 cigarettes, are the most responsive to cigarette excise taxes, and they find little evidence that smoking bans reduce cigarette consumption at any part of the smoking distribution.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Two exceptions are Laporte et al (2010), who use quantile regression and panel data from Canada to estimate a rational addiction model of smoking, and Maclean et al (2014). Maclean et al (2014) estimate smokers' responses to tobacco control policies using data from the Tobacco Use Supplement to the Current Population Survey (CPS-TUS). Using unconditional quantile regression, they find that smokers in the middle of the smoking distribution, smoking between 10 and 20 cigarettes, are the most responsive to cigarette excise taxes, and they find little evidence that smoking bans reduce cigarette consumption at any part of the smoking distribution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Maclean et al (2014) estimate smokers' responses to tobacco control policies using data from the Tobacco Use Supplement to the Current Population Survey (CPS-TUS). Although Maclean et al (2014) find statistically significant effects of cigarette excise taxes on cigarette demand, their estimated tax elasticities of demand are very small and not economically significant. Although Maclean et al (2014) find statistically significant effects of cigarette excise taxes on cigarette demand, their estimated tax elasticities of demand are very small and not economically significant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the structure of the dataset affects the number of distinct quantile solutions (e.g., Davino, Furno, & Vistocco, 2014). A second drawback of QRMs is that the medians may be affected by atypical cases Maclean et al (2014) found that the conditional QR (CQR) model produced inconsistent estimates at the lower quantiles when examining the impact of cigarette taxes on smoking consumption. Another weakness of QRMs is that the interpretation of the coefficients changes when different sets of predictors (or covariates) are included in the model (Maclean et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…A second drawback of QRMs is that the medians may be affected by atypical cases Maclean et al (2014) found that the conditional QR (CQR) model produced inconsistent estimates at the lower quantiles when examining the impact of cigarette taxes on smoking consumption. Another weakness of QRMs is that the interpretation of the coefficients changes when different sets of predictors (or covariates) are included in the model (Maclean et al, 2014). The interpretation of the coefficients also becomes more difficult when data transformations are performed on the raw scores (e.g., Hao & Naiman, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…To address this concern, we also use the Recentered Influence Function (RIF) method recently developed by Firpo et al (2009), which explicitly relaxes the common distribution assumption. 2 More specifically, when the observed outcomes (in this case, test scores) vary monotonically with the unobserved variable (in this case, student preparation), RIF for the τ th quantile as: For our analysis, instead of examining students at the same quantile across states and years (as in the QDiD case), the RIF method compares students with the same test score and hence located at potentially different quantiles of the distributions across states 2 Given its flexibility, the RIF method has recently been applied to analyze a range of issues such as cigarette taxes (Maclean et al, 2014) and child care (Havnes and Mogstad, 2015).…”
Section: Quantile Regressionsmentioning
confidence: 99%